(untitled) (Research, Society and Development, 2024)
Introduction: Autism spectrum disorder is an increasingly prevalent condition, affecting around 16% of the child population. Presents symptoms that interfere with the acquisition, retention and application of specific skills. The present study aims to bibliographically review the use of behavioral interventions in patients with autism spectrum disorder. Methods: This article consists of a literary review, searching the PubMed, Scielo and UpToDate databases. Descriptors related to behavioral interventions in patients with autism spectrum disorder with a focus on Applied Behavior Analysis were used. Publications that met the inclusion and exclusion criteria were selected. Totaling 61 articles, all discussed in the text. Discussion: Even though treatment programs for people with autism spectrum disorder vary, they have similar objectives, based on improving the patient’s quality of life. Various types of behavioral interventions are presented, however, in all cases, it is recommended that educational programs begin as soon as autism is suspected, and treatment must include a minimum workload of 25 hours per week. Applied Behavior Analysis represents a treatment modality with evidence of effectiveness in intensive behavioral therapies, presenting improvements in the intellectual functioning and adaptive behavior of patients with autism. Conclusion: Therapy for patients with autism spectrum disorder must be individualized as each individual presents different symptoms. The use of Applied Behavior Analysis has shown significant positive results. It is believed that a combination of interventions is necessary for better results.